Delayed Thrombectomy Center Arrival is Associated with Decreased Treatment Probability. (18th November 2020) - Gao, Meah M.; Wang, Jeffrey Z.; Liao, Jane; Reiter, Stephanie D.; Vyas, Manav V.; Linkewich, Elizabeth; Swartz, Richard H.; da Costa, Leodante; Kassardjian, Charles D.; Yu, Amy Y. X.
ABSTRACT: Background: Endovascular thrombectomy (EVT) is effective in reducing disability in selected patients with stroke and large vessel occlusion (LVO), but access to this treatment is suboptimal. Aim: We examined the proportion of patients with LVO who did not receive EVT, the reasons for non-treatment, and the association between time from onset and probability of treatment. Methods: We conducted a retrospective cohort study of consecutive patients with acute stroke and LVO presenting between January 2017 and June 2018. We used multivariable log-binomial models to determine the association between time and probability of treatment with and without adjustment for age, sex, dementia, active cancer, baseline disability, stroke severity, and evidence of ischemia on computerized tomography. Results: We identified 256 patients (51% female, median age 74 [interquartile range, IQR 63.5, 82.5]), of whom 59% did not receive EVT. The main reasons for not treating with EVT were related to occlusion characteristics or infarct size. The median time from onset to EVT center arrival was longer among non-treated patients (218 minutes [142, 302]) than those who were treated (180 minutes [104, 265], p = 0.03). Among patients presenting within 6 hours of onset, the relative risk (RR) of receiving EVT decreased by 3% with every 10-minute delay in arrival to EVT center (adjusted RR 0.97 CI95 [0.95, 0.99]). This association was not found in the overall cohort. Conclusions: The proportion of patients with acute stroke and confirmed LVO who do not undergo EVT is substantial. Minimizing delays in arrival to EVT center may optimize the delivery of this treatment.